2022
DOI: 10.1126/sciimmunol.abq7432
|View full text |Cite
|
Sign up to set email alerts
|

cDC1 coordinate innate and adaptive responses in the omentum required for T cell priming and memory

Abstract: In the peritoneal cavity, the omentum contains fat-associated lymphoid clusters (FALCs) whose role in response to infection is poorly understood. After intraperitoneal immunization with Toxoplasma gondii , conventional type 1 dendritic cells (cDC1s) were critical to induce innate sources of IFN-γ and cellular changes in the FALCs. Unexpectedly, infected peritoneal macrophages that migrated into the FALCs primed CD8 + T cells. Although T cell priming was cDC1 inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…To directly assess whether the enhanced eT reg cell populations observed after blockade of PD-L1 and/or CTLA-4 at homeostasis would impact the ability to generate de novo T cell responses, these pathways were blocked in naïve mice that were then immunized with a non-replicative form of Toxoplasma gondii that expresses OVA. This vaccine strain provides a system to assess the activities required to generate effector T cell responses ( 42 , 49 ). In these studies, mice were treated with isotype, α-PD-L1 or α-CTLA-4 and three days later were recipients of OTI T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To directly assess whether the enhanced eT reg cell populations observed after blockade of PD-L1 and/or CTLA-4 at homeostasis would impact the ability to generate de novo T cell responses, these pathways were blocked in naïve mice that were then immunized with a non-replicative form of Toxoplasma gondii that expresses OVA. This vaccine strain provides a system to assess the activities required to generate effector T cell responses ( 42 , 49 ). In these studies, mice were treated with isotype, α-PD-L1 or α-CTLA-4 and three days later were recipients of OTI T cells.…”
Section: Resultsmentioning
confidence: 99%
“…After 24 hours following the transfer of OTI cells, we intraperitoneally vaccinated these mice with 200,000 tachyzoites of a non-replicating vaccination-strain of T. gondii that expresses OVA (CPS-OVA). Previous studies have shown that CPS alone does not lead to activation of OTI or P14 TCR transgenic CD8 + T cells, and expression of OVA is essential for activation and expansion of the OTI T cells ( 42 ). At 24 hours after vaccination, we re-dosed these groups of mice with the original blocking antibody they had previously received to maintain the blockade treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Because the omentum is the site of T cell priming after i.p. injection of antigens ( Carlow et al, 2009 ; Rangel-Moreno et al, 2009 ; Christian et al, 2020 ), we examined the T cell response in this tissue using CD69 as a marker of TCR engagement combined with Ki67 as a marker of cells entering cell cycle ( Eickhoff et al, 2015 ; Feng et al, 2005 ; Gerner et al, 2017 ; Testi et al, 1989 ). In unimmunized mice, 5–10% of CD8 + T cells in the omentum displayed low basal levels of CD69 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation that might influence the degree of Th1 commitment in CD4 + T cells after priming is whether the pathogen is restricted to a barrier site like the gut, skin, or lungs, or is one that disseminates more widely. For systemic pathogens like Toxoplasma gondii , parasite dissemination leads to the early presence of parasites in lymphoid tissues and local production of IL-12 that results in the rapid commitment to the Th1 phenotype (58,62). When this occurs following oral infection with T. gondii , these heightened CD4 + T cell responses can result in an IFN-γ-mediated lethal ileitis (63).…”
Section: Discussionmentioning
confidence: 99%